Successful Sleeve Resection as a Marker for Proficiency for Robotic Pulmonary Resection - Cosgun, Tugba; Kaba, Erkan; Ayalp, Kemal; Toker, Alper (The Thoracic and Cardiovascular Surgeon, 2019)
Background Robot technology is a revolutionary technique to overcome limitations of minimal invasive surgery. The proficiency level varies from study to study. We considered the first sleeve lobectomy as a benchmark procedure to evaluate the proficiency level.Methods We retrospectively analyzed 197 patients who underwent robot-assisted thoracoscopic surgery (RATS) for primary lung cancer between December 2011 and May 2018. Patients were divided into two groups based on undergoing surgery earlier period (EP) or later period (LP) than the first sleeve lobectomy by RATS (May 25, 2015). The preoperative, operative, and short- and long-term postoperative outcomes were compared. Seven-year survival was also compared between two periods for T1N0 and T2N0 diseases.Results Preoperative features were similar. The mean operative time was 166.8 ± 55.1 and 142.4 ± 43.9 minutes in EP and LP, respectively (p = 0.005). The mean number of dissected lymph nodes in LP was also significantly higher than that in EP (24.4 ± 9.4 vs. 20.8 ± 10.4, p = 0.035). The complication rate was significantly lower in LP (29/86 vs. 25/111, p = 0.048). The extended resection (ER) rate was significantly higher in LP (p = 0.023). The 7-year survival was comparable in EP and LP in both patients with T1N0 and T2N0 (p = 0.28 and p = 0.11, respectively).Conclusion Perioperative outcomes, such as duration of surgery, number of dissected lymph nodes, complications, and ERs are favorable in patients who underwent surgeries after the first sleeve resection. The first sleeve lobectomy may be considered as the benchmark procedure for the proficiency level in RATS.
Keywords: lung cancer; learning curve; proficiency; robot-assisted thoracoscopic surgery